Survey in archery interest at suryakancana university of cianjur - Andi Kurniawan Pratama; Asep Ramdan Afriyuandi; Muh Syahreza Rizkiana; Ani Kurniawati (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
Research aims to find out how the interest of suryakancana university students towards the sport of archery. The research used is a type of quantitative research with a descriptive approach, which is in the form of a survey with a sample of 100 people. Based on the results of the study it can be concluded that the interest of students of Suryakancana Cianjur University towards archery sports falls into the low category, it is evident that from 100 students there are 21 students or 21% have high interest, 30 students or 30% have moderate interest, 40 students or 40% in the low category and 9 students in very low categories. Based on this research it is known that most students of Suryakancana Cianjur University have an interest in archery in the low category. Key words: archery, interest